X-Ray Diffraction Studies of Chitosan Acetate-Based Polymer Electrolytes - Z, Osman; Z.A, Ibrahim; A.K, Arof (Malaysian Journal of Science, 2002)
Chitosan is the product when partially deacetylated chitin dissolves in dilute acetic acid. This paper presents the x-ray diffraction patterns of chitosan acetate, plasticized chitosan acetate and plasticized-salted chitosan acetate films. Thc results show that the chitosan acetate-based polymer electrolyte films are not completely amorphous but it is partially crystalline. X-ray diffraction study also confirms the occurrence of the complexation between the chitosan and the salt and the interaction between salt and plasticizer. The salt-chitosan intcraction and salt-plasticizer interaction is clearly justified by infrared spectroscopy.